PREDATOR MANAGEMENT OF TWO DIFFERENT STRAINS (KUSMI AND RANGEENI LAC) OF KERRIA LACCA (KERR) ON ZIZYPHUS MAURITIANA - BHAGIRATH PATEL; SANDEEP JANGHEL; MONI THOMAS (The Bioscan, 2015)
The predator management of two different strains (Kusmi and Rangeeni lac) of Kerria lacca (Kerr) on Zizyphus mauritiana was studied in the field of 10 lac growers in Kachana village Barghat Block, Seoni District, Madhya Pradesh, from July 2012 to December 2012. A combination of two sprays of Cartap hydrochloride and Mancozeb (T1 and T3), Control (Lac growers practices i.e., no use of pesticides) T2 and T4. Were the two set of treatments in both Lac strains. Application of pesticides reduced predator infestation in both strains over Lac growers practices. Rangeeni strain was more susceptible parasitoids than the Kusmi even in pesticides treatment. Pesticide applications significantly reduced the mean number predators and parasitoids infested lac cells at harvest per 30 cm sticklac. It was in (44.00) in case of T4 followed by T3 (29.50), T2 (22.50) and T1 (20.50) at harvest.